2019
DOI: 10.1111/ncn3.12268
|View full text |Cite
|
Sign up to set email alerts
|

Familial neuronal intranuclear inclusion disease complicated by subcortical hemorrhage

Abstract: An 80‐year‐old woman presented with loss of appetite. At age 78, she was diagnosed as familial neuronal intranuclear inclusion disease (NIID) based on (i) leukoencephalopathy with hyperintensities along the corticomedullary junction on diffusion‐weighted imaging (DWI) revealed by brain magnetic resonance imaging (MRI), (ii) skin biopsy samples showing ubiquitin‐positive intranuclear inclusions in adipocytes, and (iii) family history. Her cognitive function was preserved while apathy was apparent. However, on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Our study reports two rare central nervous system complications associated with NIID, namely subacute encephalitic episodes as well as spontaneous lobar ICH. To our knowledge there had only been one prior report of spontaneous ICH associated with NIID 27 . Liu et al and Langford reported the presence of perivascular inflammatory changes in patients with clinical presentations consistent with that of a subacute encephalitic episode, 28,29 suggesting these phenomena may be secondary to an underlying vascular pathology.…”
Section: Discussionmentioning
confidence: 96%
“…Our study reports two rare central nervous system complications associated with NIID, namely subacute encephalitic episodes as well as spontaneous lobar ICH. To our knowledge there had only been one prior report of spontaneous ICH associated with NIID 27 . Liu et al and Langford reported the presence of perivascular inflammatory changes in patients with clinical presentations consistent with that of a subacute encephalitic episode, 28,29 suggesting these phenomena may be secondary to an underlying vascular pathology.…”
Section: Discussionmentioning
confidence: 96%